Enhancing Soil Nitrogen Use and Biological Nitrogen Fixation in Wetland Rice - Kundu, D.K.; Ladha, J.K. (Cambridge University Press, 1995)
The limited fossil fuel reserve available for manufacturing fertilizer nitrogen and the adverse effects of continued use of high fertilizer nitrogen doses on the environment call for a more efficient use of indigenous soil nitrogen. This paper presents several ways of enhancing soil nitrogen use in wetland rice. These involve utilizing nitrogen present in the deeper soil layers, increasing soil nitrogen mineralization rate, decreasing the loss of mineralized nitrogen from the rooting zone, and adjusting rice variety, soil flooding, and transplanting time. To sustain nitrogen fertility and productivity of ricelands, however, the original soil nitrogen levels must be maintained through natural resources like recycled crop residues and enhanced biological N2 fixation. Various ways of stimulating biological nitrogen fixation by both indigenous and exogenous agents are discussed. Since enhancement of soil nitrogen use in rice and maintenance of the original nitrogen level in soil by stimulating biological nitrogen fixation have not been examined together in the field, elaborate field experiments should be conducted to assess the impacts of such combined practices on long-term soil nitrogen fertility and productivity.